Teacher's Politeness Strategies In EFL Classroom Interaction At Junior High School - Shafa Zata Zahirah; Siska; Edwar Kemal (Darul Yasin Al Sys, 2026)
Teacher–student interaction in English as a Foreign Language (EFL) classrooms entails not only the delivery of instructional content but also the strategic use of politeness to facilitate effective communication and sustain interpersonal relationships. This study aimed to identify and analyze the politeness strategies employed by an English teacher during classroom interactions at MTSS Al-Falah. Using a descriptive qualitative design, the study involved one English teacher and Grade IX-1 students. Data were collected through classroom observations, video recordings, and field notes and analyzed using Brown and Levinson’s politeness framework, with the interactional context examined through Hymes’ SPEAKING model. The analysis identified 21 teacher utterances containing politeness strategies: 17 instances of bald-on-record, three of positive politeness, and one of negative politeness; no off-record strategy was observed. The predominance of bald-on-record strategies indicates that the teacher prioritized directness to ensure instructional clarity and facilitate classroom management. These findings demonstrate that teachers’ politeness strategies constitute context-dependent pragmatic choices shaped by instructional purposes and classroom conditions. The study contributes to EFL classroom pragmatics by highlighting the importance of strengthening teachers’ pragmatic awareness and their capacity to adapt communication strategies to specific pedagogical and interactional contexts.